2021
DOI: 10.1109/jbhi.2020.3027680
|View full text |Cite
|
Sign up to set email alerts
|

Identification of lncRNA Signature Associated With Pan-Cancer Prognosis

Abstract: Long noncoding RNAs (lncRNAs) have emerged as potential prognostic markers in various human cancers as they participate in many malignant behaviors. However, the value of lncRNAs as prognostic markers among diverse human cancers is still under investigation, and a systematic signature based on these transcripts that related to pan-cancer prognosis has yet to be reported. In this study, we proposed a framework to incorporate statistical power, biological rationale, and machine learning models for pan-cancer pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 118 publications
0
8
0
Order By: Relevance
“…Moreover, Bao et al. found that PCAT29 was expressed in OC and the positive rate of PCAT29 was 82/116; they also identified PCAT29 as a signature associated with prognosis in pan-cancer (including OC) ( 56 ). PR11-508M8.1 was proposed as a biomarker for predicting the risk of papillary thyroid carcinoma relapse ( 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Bao et al. found that PCAT29 was expressed in OC and the positive rate of PCAT29 was 82/116; they also identified PCAT29 as a signature associated with prognosis in pan-cancer (including OC) ( 56 ). PR11-508M8.1 was proposed as a biomarker for predicting the risk of papillary thyroid carcinoma relapse ( 57 ).…”
Section: Discussionmentioning
confidence: 99%
“… 28 In a pan-cancer study, a signature based on 5 lncRNAs was found to behave well in predicting survival outcomes of cancers based on the TCGA, TARGET, and National Cancer Institute cohorts. 29 After exploring the lncRNAs in colorectal cancer, HOXA11-AS, MEG3, SLCO4A1-AS1, SPINT1-AS1, and DANCR lncRNAs were discovered strong power for the diagnosis. 30 Four-methylated LncRNAs were considered as biomarkers for predicting the survival of osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of biotechnology, the results of the Human Genome Project show that less than 2% of the nucleic acid sequence is used to encode proteins, and the rest part doesn’t express proteins, which are called non-coding RNAs(ncRNA) ( He et al, 2021 ; Yip et al, 2021 ; Zhou et al, 2021 ). ncRNA was originally thought to be transcriptional noise, but with the advancement of researches, it is been discovered that ncRNA is pivotal for normal development and disease progression ( Bao et al, 2021 ; Chen et al, 2021 ; Smolarz et al, 2021 ). ncRNAs exceeding 200 nt are called lncRNAs.…”
Section: Introductionmentioning
confidence: 99%